Analysis of willingness to pay for the purchase of organic bok choy using the contingent valuation method (CVM) in Cepogo District, Boyolali Regency - Indriani, Widya; Sutrisno, Joko; Marwanti, Sri (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2025)
The high demand for organic bok choy vegetables is driven by the increasing prevalence of degenerative diseases, which are often associated with unhealthy consumption patterns. However, farmers in Cepogo District, Boyolali Regency, still face challenges in determining the optimal selling price. This study aims to estimate consumers' willingness to pay (WTP) for organic bok choy vegetables in Cepogo District, Boyolali Regency, and analyze the factors influencing consumers' WTP for purchasing organic bok choy in the same area. The research employs the Contingent Valuation Method (CVM) to estimate the WTP value for organic bok choy. Additionally, logistic regression analysis is used to evaluate the factors affecting WTP. The findings indicate that the average WTP for organic bok choy in Cepogo District, Boyolali Regency, is IDR 5,760.00 per 500 grams. Education level, awareness of organic bok choy and belief in organic bok choy are identified as factors positively influencing consumers' WTP.